Evaluation of the Expression Pattern of 4 microRNAs and their Correlation with Cellular/viral Factors in PBMCs of Long Term Non-progressors and HIV Infected Naïve Individuals - Jamshidi, Sogol; Bokharaei-Salim, Farah; Nahand, Javid S.; Monavari, Seyed Hamidreza; Moghoofei, Mohsen; Garshasbi, Saba; Kalantari, Saeed; Esghaei, Maryam; Mirzaei, Hamed (Current HIV Research, 2022)
Background: Long-term non-progressors (LTNPs) are small subsets of HIV-infected subjects that can control HIV-1 replication for several years without receiving ART. The exact mechanism of HIV-1 suppression has not yet been completely elucidated. Although the modulatory role of microRNAs (miRNAs) in HIV-1 replication has been reported, their importance in LTNPs is unclear. Objective: The aim of this cross-sectional study was to assess the expression pattern of miR-27b, -29, -150, and -221, as well as their relationship with CD4+ T-cell count, HIV-1 viral load, and nef gene expression in peripheral blood mononuclear cells (PBMCs) of untreated viremic patients and in LTNPs. Methods: MiRNAs expression levels were evaluated with real-time PCR assay using RNA isolated from PBMCs of LTNPs, HIV-1 infected naive patients, and healthy people. Moreover, CD4 T-cell count, HIV viral load, and nef gene expression were assessed. Results: The expression level of all miRNAs significantly decreased in the HIV-1 patient group compared to the control group, while the expression pattern of miRNAs in the LNTPs group was similar to that in the healthy subject group. In addition, there were significant correlations between some miRNA expression with viral load, CD4+ T-cell count, and nef gene expression. Conclusion: The significant similarity and difference of the miRNA expression pattern between LNTPs and healthy individuals as well as between elite controllers and HIV-infected patients, respectively, showed that these miRNAs could be used as diagnostic biomarkers. Further, positive and negative correlations between miRNAs expression and viral/cellular factors could justify the role of these miRNAs in HIV-1 disease monitoring.
Keywords: viremic controllers (VCs)